Distinction between charisma and vision. - Lim, Jacqueline Ai Hoon. (2008)
In this paper, we believe that charisma and vision are two distinct constructs, unlike past research. A study was conducted on student leaders in NTU for measuring the two constructs and their effects on motivation, satisfaction, commitment and perforrmance of the followers. From our results, we found charisma to be distinct from vision. Both were found to have two dimensions each.